Frontline First : A Forward-Looking Agenda for Health Systems Transformation - World Bank Group (World Bank, Washington, DC, 2019)
The frontline of the health system comprises the primary health care (PHC) system, the networks of frontline health workers, and other public- or private-sector services or institutions that serve as first-touch points with the public health and health care systems, as well as channels outside the formal health care infrastructure that help communities, households, and individual co-produce positive health outcomes. These frontline networks represent the first point of contact between individuals and the health system: they are the backbones of effective health systems, best positioned to offer first-level assessment, treatment, and health education. Functional frontline networks also connect families and communities to critical care and the broader health system; they operate most effectively as an integrated part of a multilayered PHC team, requiring a functional two-way referral system between frontlines and first-level referral facilities.